Coping and Help-Seeking Strategies Used by Students on the Intensive Foundation Program at the University of Brunei Darussalam - Lawrence Mundia; Masitah Shahrill (SAGE Open, 2018)
Human resource development is one of the major goals of Brunei’s current development plan to be achieved under Wawasan 2035 policy. The University of Brunei Darussalam’s foundation program aims to increase students’ access to higher education among disadvantaged and underrepresented groups. The present field survey investigated how the coping strategies and help-seeking behaviors of 146 (103 females and 43 males) Brunei foundation students would assist. Participants from government secondary schools scored significantly higher on the productive coping and reference to others coping styles than peers from private schools. Main effective predictors of achievement included productive coping, referencing to others, and using resources (library, Internet, peers, lecturers, and self-efficacy). Two-way interactions of the male gender with the library, Internet, lecturers, peers, and self-efficacy would help improve men’s achievement. The interaction of Internet and nonproductive coping also predicted achievement. Interventions for vulnerable and at-risk students were recommended to increase the success rate.